Atributos de qualidade de solos sob dois diferentes tipos de manejo no município de Ibiúna/SP, Brazil - Manfre, Luiz Augusto [UNESP]; Silva, Alexandre Marco da [UNESP]; Urban, Rodrigo Custodio [UNESP] (Interciencia, 2011)
Agricultural activity has direct consequences on the soil and water quality. Thus, assessing environmental impacts of this vital economic activity, through soil attribute analysis, is essential to the proposal of alternatives. The aim of this study was to analyze soil quality under different land management practices, conventional and organic. The study was carried out in a watershed of the Ibiuna municipality, SP, Brazil, an important supplier of agricultural products for the São Paulo metropolitan area. A hundred samples were collected, 20 in each type of land use: reforested areas, native vegetation, pasture, conventional cultivation and organic cultivation. The soil resistance to penetration, its pH (in water and KO), electrical conductivity, bulk density, particle density, porosity, soil color, soil texture and the percentages of carbon and nitrogen were analyzed. The data were statistically analyzed, searching for significant differences. The results of soil analysis showed great similarity between the organic and conventional culture, with no statistical differences. However, organic cultivation showed greater similarity to the soil of native vegetation in the percentage of carbon and nitrogen in soils compared to conventional culture. Thus, the discussion begins on a topic very little explored so far, and the results obtained should be further studied.
Soil quality attributes under two different managements in the municipality of Ibiuna, SP, Brazil